2004
DOI: 10.1038/sj.ijo.0802846
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of drop-out in overweight and obese outpatients

Abstract: The overweight and obese outpatients at higher risk of ambulatory treatment drop-out are more likely to work full hours, have less obesity-related complications and be less depressed. In our study, the full-time job condition seems to be the strongest predictor of premature withdrawal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
159
1
15

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(200 citation statements)
references
References 41 publications
25
159
1
15
Order By: Relevance
“…Attrition rates of 10-80% have been reported across various behavioural, pharmacological and surgical weight loss treatments (Inelmen et al, 2005). In addition, about half the weight lost is often regained within 1 year and almost all is typically regained within 3-5 years post-treatment (Jeffery et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Attrition rates of 10-80% have been reported across various behavioural, pharmacological and surgical weight loss treatments (Inelmen et al, 2005). In addition, about half the weight lost is often regained within 1 year and almost all is typically regained within 3-5 years post-treatment (Jeffery et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Subjects were asked to indicate their habitual food choices and usual patterns of consumption of the various foodstuffs on a daily, weekly, monthly or yearly basis. This diet assessment method had already been validated in a previous study (Inelmen et al, 2005) and details of the procedure can be found elsewhere (Inelmen et al, 2000). Mean daily intake was calculated, including total energy (kcal/day), macronutrients (proteins, carbohydrates, lipids) and calcium.…”
Section: Protocolmentioning
confidence: 99%
“…There were 15 control papers published in five of these journals (Figure 1), eight containing data on children or a definition of obesity in just three journals (Table 2). One used BMI only as a continuous variable (McCarthy et al, 2005), one used the adult definition of overweight from age 15 years (Inelmen et al, 2005), one advocated the IOTF definition but did not cite a reference (Viner and Nicholls, 2005) and the remaining five sets of authors used a centile of their national distribution.…”
Section: Resultsmentioning
confidence: 99%